The Establishment and Administration of Maẓālim Court System in Sokoto Metropolis in the 19th Century - Tukur Muhammad Mukhtar (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2020)
This paper studied the establishment and administration of Maẓālim Court system in Sokoto Caliphate in the 19th century. This was with a view to investigating the efforts and commitment of the founders of the Sokoto Caliphate to the administration of justice which was one of the central arguments of the leaders of the 1804 Sokoto Jihad against the Hausa aristocrats before the 19th century. The case in point – Maẓālim Court was the apex court in the Islamic judicial system, and open establishment of the Caliphate the leadership in justification of their commitment to justice established this court in Sokoto which was the seat of power of the Caliph. Using a qualitative methodology, the paper found that Maẓālim court was established and was operated by the Caliph in Sokoto during the 19th century. In addition, it was however discovered that the court was operated in Sokoto with three mandates: accepting and administering fresh judicial complaints; administering appeals from the lower courts, and operating an Ombudsman mandate. But its operation was not exclusively by the Caliph alone; rather it was operated in some instances by the Wullāt (representatives) of the Caliph as indicated in the text. Thus, this paper concluded that the establishment and administration of the Maẓālim court in Sokoto was a clear indication of the commitment of the founders of the 19th century Sokoto Caliphate to the administration of justice as a justification to their course of rising against the injustices of the former Hausa aristocrats.